ESCRS Clinical Trends Survey 2016–2021: 6-year assessment of practice patterns among society delegates. Issue 2 (February 2023) - Kohnen, Thomas; Findl, Oliver; Nuijts, Rudy; Ribeiro, Filomena; Cochener-Lamard, Béatrice
Abstract : ESCRS Clinical Trends Surveys provide valuable insights into delegate practice patterns and the shift of clinical opinion over time. Abstract : Purpose: To evaluate clinical opinions and practice patterns of delegates to the ESCRS. Setting: Clinical Trends Surveys were administered during annual ESCRS congresses held between 2016 and 2021, and data collected online and in-person. Design: Survey questions addressed several specialty areas, including cataract surgery, presbyopia-correcting and toric intraocular lenses (IOLs), ocular surface disease, and glaucoma. Methods: Survey results were compared and analyzed across 6 years. 4 main profile questions were used for cross-tabulation analyses of questions pertaining to refractive surgery—practice location, years in practice, primary surgery setting, and average annual volume of cataract surgery. Results: The highest number of responses (3019) was collected in 2019, with the lowest (569) received in 2020. The use of presbyopia-correcting and toric IOLs has increased significantly from 2016 to 2021, with certain respondent segments using them more frequently than others. Although optical biometry remains the preferred method for obtaining preoperative measurements, the use of tomography (Scheimpflug) has significantly increased. In 2021, 61.1% and 44.9% of respondents always performed preoperative checks of the ocular surface before refractive and cataract surgery, respectively. The number of respondents who perform glaucoma surgery has significantly decreased over the years, with an increasing number of delegates reporting having only a medical glaucoma practice. On average, 5.4% of patients with cataract and glaucoma underwent combined minimally invasive glaucoma surgery and cataract procedures in 2021. Conclusions: Evaluation of the Clinical Trends Survey data provides valuable insights into the shifting practice patterns and clinical opinions of ESCRS delegates.